THE EFFECT OF DIRECT LEARNING MODEL ON THE LEARNING OUTCOMES OF IPS STUDENTS IN CLASS VIII SMP NEGERI 1 MUARA LAKITAN - Tiara Anggra Yeni, Tiara Anggra Yeni, Supriyanto, Yeni Asmara (JURNAL EDUSCIENCE, 2023)
This study aims to determine the effect of the Direct Learning Model on Social Studies Learning Outcomes for Grade VIII Students at SMP Negeri 1 MuaraLakitan. The research method used is a quantitative method, with a pure experimental research type. The research design was in the form of a pre-test – post-test control group design. The data collection technique used is the test technique. The type of research instrument to be used is in the form of multiple choice totaling 35. The data analysis technique in this study is a quantitative technique. The population in this study was all class VIII for the 2022/2023 academic year with a total of 52 students. The samples taken in the study were class VIIIa as the control class with 25 students and class VIIIb as the experimental class with 27 students. The control class was taught using the method conventional and experimental classes were given treatment using the Direct learning model on the learning material of the Emergence of National Movement Organizations in Indonesia, the average post-test score of the control class students was 73.8 and the experimental class was 83.2. From the results of the analysis of the final test data, it was obtained that tcount ≥ ttable, namely tcount = 4.565 and ttable = 2.000 at a significant level of ɑ= 0.05. Based on these calculations, it can be concluded that there is an influence of the Direct Learning Model on Social Studies Learning.  Keywords: Problem Based Learning and Learning Outcomes Abstrak Penelitian ini bertujuan untuk dapat mengetahui Pengaruh Model Direct Learning Terhadap Hasil Belajar IPS Siswa Kelas VIII Di SMP Negeri 1 Muara Lakitan. Metode penelitian yang digunakan adalah metode kuantitatif, dengan jenis penelitian ekperimen murni. Desain penelitian ini berbentuk pre-test–post-test kontrol group design. Teknik pengumpulan data yang digunakan adalah teknik tes. Jenis instrumen penelitian yang akan digunakan adalah yang berbentuk pilihan ganda berjumlah 35. Teknik analisis data dalam penelitian ini adalah teknik kuantitatif. Populasi dalam penelitian ini yaitu seluruh kelas VIII tahun pelajaran 2022/2023 dengan jumlah siswa 52. Sampel yang diambil dalam penelitian adalah kelas VIIIa sebagai kelas kontrol dengan jumlah siswa 25 dan kelas VIIIb sebagai kelas eksperimen dengan jumlah siswa 27. Kelas kontrol diberikan pembelajaran menggunakan metode konvensional dan kelas eksperimen diberikan perlakuan dengan menggunakan model Direct learning pada materi pembelajaran Munculnya Organisasi-Organisasi Pergerakan Nasional di Indonesia, nilai post test rata-rata siswa kelas kontro l73,8 dan kelas eksperimen 83,2. Dari hasil analisis data tes akhirdiperoleh thitung≥   ttabel yaitu thitung =4,565 dan ttabel = 2,000 pada taraf signifikanɑ= 0,05. Berdasarkan perhitungan tersebut jadi dapat disimpulkan ada Pengaruh Model Direct Learning Terhadap Hasil Belajar IPS Siswa Kelas VIII Di SMP Negeri 1 Muara Lakitan.Kata Kunci : Model Direct Learning dan hasil belajar